Pixels & paintings foundations of computer-assisted connoisseurship - Stork, David G. ca. 20./21. Jh (Wiley, 2024)
The pioneering presentation of computer-based image analysis of fine art, forging a dialog between art scholars and the computer vision community In recent years, sophisticated computer vision, graphics, and artificial intelligence algorithms have proven to be increasingly powerful tools in the study of fine art. These methods—some adapted from forensic digital photography and others developed specifically for art—empower a growing number of computer-savvy art scholars, conservators, and historians to answer longstanding questions as well as provide new approaches to the interpretation of art. Pixels & Paintings provides the first and authoritative overview of the broad range of these methods, which extend from image processing of palette, marks, brush strokes, and shapes up through analysis of objects, poses, style, composition, to the computation of simple interpretations of artworks. This book stresses that computer methods for art analysis must always incorporate the cultural contexts appropriate to the art studies at hand—a blend of humanistic and scientific expertise. Describes powerful computer image analysis methods and their application to problems in the history and interpretation of fine art. Discusses some of the art historical lessons and revelations provided by the use of these methods. Clarifies the assumptions and applicability of methods and the role of cultural contexts in their use. Shows how computation can be used to analyze tens of thousands of artworks to reveal trends and anomalies that could not be found by traditional non-computer methods.
Keywords: Kunstwissenschaft; Digitalisierung